2016
DOI: 10.1002/2016pa002958
|View full text |Cite
|
Sign up to set email alerts
|

The MMCO‐EOT conundrum: Same benthic δ18O, different CO2

Abstract: Knowledge on climate change during the Cenozoic largely stems from benthic δ18O records, which document combined effects of deep‐sea temperature and ice volume. Information on CO2 is expanding but remains uncertain and intermittent. Attempts to reconcile δ18O, sea level, and CO2 by studying proxy data suffer from paucity of data and apparent inconsistencies among different records. One outstanding issue is the difference suggested by proxy CO2 data between the Eocene‐Oligocene boundary (EOT) and the Middle‐Mio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 71 publications
0
18
1
Order By: Relevance
“…5c, yellow shading). Using a different tuning, our Middle Miocene values are closer to the observations, but then the Early Oligocene values are also much lower (see Stap et al, 2016b, for an analysis). In short, we are not able to simulate a difference in CO 2 between right before the Eocene-Oligocene transition and during the Middle Miocene climatic optimum.…”
Section: Comparison To Proxy Co 2 Datamentioning
confidence: 84%
See 4 more Smart Citations
“…5c, yellow shading). Using a different tuning, our Middle Miocene values are closer to the observations, but then the Early Oligocene values are also much lower (see Stap et al, 2016b, for an analysis). In short, we are not able to simulate a difference in CO 2 between right before the Eocene-Oligocene transition and during the Middle Miocene climatic optimum.…”
Section: Comparison To Proxy Co 2 Datamentioning
confidence: 84%
“…The tuning targets and consequent values for C abl have been described in Stap et al (2014). The influence of this parameter for inception of the East Antarctic ice sheet has been discussed in Stap et al (2016b), who showed that changing the value from −30 to −5 results in glacial inception at roughly 450 ppm instead of 700 ppm. The ice sheet models calculate the surface height change and ice sheet extent using the shallow ice approximation with 15 to 25 km of resolution depending on the ice sheet (De Boer et al, 2010).…”
Section: Modelmentioning
confidence: 99%
See 3 more Smart Citations